A Feasibility study on a fishmeal processing plant - Agutaya, Yvonne Felisse F.; Diaz, Yolanda; Gutierrez, Marley; Manaloto, Diosdado M.; Ramel, Erwin Arsenio G. III.; Santos, Jorge G.; Suganob, Perlita; Ulep, Corabelle R. (Diliman, Quezon City College of Engineering, 1983)
The study assesses the feasibility of putting up a fishmeal processing plant for the members of KAISAs (Kalipunan ng mga ISA), province wide federations engaged in agricultural, livestock and fishing income generating enterprises. Fishmeal, a major constituent of animal feeds, appears to have a ready market found in feed mills run by KAISAs. Historical demand and supply figures show that fishmeal is a highly viable commercial product. Its national production over the past ten years could not cover eighty per cent of what is demanded by feed mills all over the country. The market of the proposed fishmeal plant includes KAISA and non-KAISA feed mill enterprises. The proposed plant shall operate at two eight hour shifts per day with a daily capacity of ten tons of raw materials. This is equivalent to two tons of fishmeal product. Each shift will have five helpers, one supervisor, and one mechanical operator. The administrative duties of the firm will be handled by one plant maager, one finance officer and one bookkeeper. The total project cost is P2,828,826.26, ninety percent of which will be borrowed; ten percent will be raised by the participating KAISAs. The project's economic feasibility was evaluated by using Net Present Value and IRR analyses. The project's Net Present Value of P320,147.23 and high IRR indicate the economic feasibility of the project.
Feasibility study
Typescript
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: Farm Systems Development Corporation (FSDC); Fish meal industry; Fish canneries; Participatory monitoring and evaluation (Project management)